Medical Devices-Related Counseling Practices Among Community Pharmacists: A Nationwide Cross-Sectional Study from Saudi Arabia - Fathelrahman AI (Dove Medical Press, 2021)
Ahmed Ibrahim Fathelrahman Department of Clinical Pharmacy, College of Pharmacy, Taif University, Taif, Saudi ArabiaCorrespondence: Ahmed Ibrahim FathelrahmanDepartment of Clinical Pharmacy, College of Pharmacy, Taif University, P.O. Box 888, Taif, 21974, Saudi ArabiaTel +966 537298070Email afathelrahman@yahoo.comObjective: The current study was conducted to assess medical devices-related counseling practices among community pharmacists in Saudi Arabia.Methodology: This was a cross-sectional study conducted among community pharmacists from Saudi Arabia using a convenience sampling technique. An online questionnaire based on Google forms was used to collect data. Descriptive and inferential analyses were conducted using SPSS statistics 22. Student t-test, one way ANOVA, and Pearson correlation statistics were used where applicable. Results with a p-value of < 0.05 were considered statistically significant.Results: One thousand and six community pharmacists responded to the survey. Males' rating of their ability to operate medical devices was significantly higher than females (overall average score of 3.8 versus 3.5, p=0.033). As years of experience increased there were slight but significant increases in the overall scores on ability to operate medical devices (p=0.002) and confidence to counsel patients about the devices (p=0.032). Those who got a board certification used devices for self-treatment significantly more than their counterparts (on average 6.9 devices versus 5.2, p=0.003). Those who received clinical training reported higher rates of ability to use/operate devices (p=0.011), confidence to counsel patients on devices (p=0.001), and counseling practice (p=0.044) than those who did not receive clinical training.Conclusion: The present study revealed good to very good self-reported medical devices-related counseling practices. There is a need for more future rigorous research to evaluate pharmacists' actual practice in this area. Pharmacy educators and CPD programs should pay attention to updating pharmacists' knowledge and skills and improve their contribution to medical devices supportive services.Keywords: community pharmacists, correlations, counseling practices, medical devices, Saudi Arabia